2017
DOI: 10.1002/ijgo.12353
|View full text |Cite
|
Sign up to set email alerts
|

Disrespect and abuse during childbirth in fourteen hospitals in nine cities of Peru

Abstract: Nearly all participants reported having experienced at least one category of disrespect and abuse during childbirth care, which was associated with type of delivery, being referred, and geographic region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 18 publications
2
31
4
8
Order By: Relevance
“…This finding is incomparable with study were done in India 71.3% [12], in Pakistan 97.4% [54], in Pakistan 99.7% [55], and in Peru 97.4% [56]. The possible explanation might be the way of defining of disrespect and abuse, the study population, and the health facility set up difference.…”
Section: Discussioncontrasting
confidence: 70%
“…This finding is incomparable with study were done in India 71.3% [12], in Pakistan 97.4% [54], in Pakistan 99.7% [55], and in Peru 97.4% [56]. The possible explanation might be the way of defining of disrespect and abuse, the study population, and the health facility set up difference.…”
Section: Discussioncontrasting
confidence: 70%
“…Person-centered care during childbirth is recognized as a valued dimension of quality of maternal and newborn care [ 1 ]. Poor person-centered care during childbirth has, however, increasingly been documented around the globe [ 2 5 ]. This recognition has prompted recent recommendations by the World Health Organization (WHO) on intrapartum care for a positive childbirth experience [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Countries like Brazil[ 16 ] and Mexico[ 15 ] also had a low prevalence of disrespect and abuse. However, studies from Sudan,[ 17 ] Pakistan,[ 18 19 ] and Peru[ 20 ] have reported a higher prevalence. The difference in these findings may be due to the methodologies, definitions adopted, and sociocultural factors in different studies.…”
Section: Discussionmentioning
confidence: 99%